Collaboration between centres of the World Health Organization. Italy supports a Mexican University / Una collaborazione Italia-Messico in ambito dell’Organizzazione Mondiale della Sanità - Alegria-Torres, J.; Baccarelli, A. (La Medicina del Lavoro, 2010)
Background: México is the third most populous country in America. A sizeable percentage of Mexicans live under unfavorable conditions such as malnutrition, marginalization and overcrowding. Environmental injustice includes: indigenous exposed to wood smoke, families living in mining zones, children working and living in garbage dumps and brick factories. Polycyclic aromatic hydrocarbons, pesticides, electronic waste and heavy metals exposure represent a health risk. These pollutants can induce biochemical lesions as DNA damage and epigenetic changes which could modify the gene expression profile of each individual. Objectives: The aim of this work is to create an Italy-Mexico collaboration (within the context of WHO collaborating centres) between the Center of Molecular and Genetic Epidemiology, University of Milan and the University of San Luis Potosi, will allow molecular approaches to develop early indicators of susceptibility to adult disease and cancer.Una collaborazione Italia-Messico in ambito dell’Organizzazione Mondiale della SanitàIl Messico è il terzo paese più popoloso d'America. Una percentuale considerevole di messicani vivono in condizioni sfavorevoli come la malnutrizione, l'emarginazione e sovraffollamento. L’ingiustizia ambientale comprende: indigeni esposti al fumo prodotto dal legno che brucia, famiglie che vivono in zone minerarie, bambini che vivono e lavorano nelle discariche e nelle fabbriche di laterizi. L’esposizione ad idrocarburi policiclici aromatici, pesticidi, rifiuti di apparecchiature elettriche ed elettroniche e metalli pesanti rappresentano un rischio per la salute. Questi inquinanti possono indurre lesioni biochimiche quali il danno al DNA e i cambiamenti epigenetici che potrebbero modificare il profilo di espressione genica di ciascun individuo. Una collaborazione Italia-Messico (nel contesto di centri collaboratori OMS) tra il Centro di Epidemiologia Molecolare e Genetica dell'Università degli Studi di Milano e l'Università di San Luis Potosi, consentirà un approccio molecolare mirato a proporre indicatori precoci di predisposizione alle malattie negli adulti e al cancro.